The Influence of the Company's Environment With Marketing Communications on Consumer Subscription Behavior at PT. Tri Putra Erguna - Fauzan Adli; Muhammad Alfikri (LEGAL BRIEF, 2022)
This article discusses the marketing communication strategy used by PT Tri Putra Erguna in its consumer goods marketing activities. The author will observe how PT Tri Putra Erguna's marketing communication strategy in marketing activities, and what is interesting in this research is that the company's marketing communication activities have received a lot of support from the brand owner or principal. The research paradigm employed is constructivist, and the research method employed is case study research with a qualitative approach. In this study, data was gathered through observation and interviews. This study aims to discover empirical evidence from the research object, how to reveal marketing communication strategies in the marketing activities of consumer goods products at PT Tri Putra Erguna, and to construct meaning on the implementation of marketing communication activities.